2013
DOI: 10.1097/pas.0b013e31827edfda
|View full text |Cite
|
Sign up to set email alerts
|

A Benign Cutaneous Plexiform Hybrid Tumor of Perineurioma and Cellular Neurothekeoma

Abstract: There are several recent reports describing hybrid peripheral nerve sheath tumors showing a biphasic component of neoplastic cells. These combinations include a mixture of neurofibroma and schwannoma, schwannoma and perineurioma, neurofibroma and perineurioma, and perineurioma and granular cell tumor. A case of a triphasic combination of neurofibroma, schwannoma, and perineurioma has also been described. We describe the clinicopathologic and immunohistochemical characteristics of 9 cases of a benign cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…The patient was a 24-year-old female with an internal auditory canal mass. The same year, Requena et al [29] published a series of 9 hybrid PNSTs, all located on the lips and histologically showing distinct features of perineurioma and cellular neurothekeoma. Hayashi et al reported multifocal intradural tumors at T11/12 and L1 in a 63-year-old-male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient was a 24-year-old female with an internal auditory canal mass. The same year, Requena et al [29] published a series of 9 hybrid PNSTs, all located on the lips and histologically showing distinct features of perineurioma and cellular neurothekeoma. Hayashi et al reported multifocal intradural tumors at T11/12 and L1 in a 63-year-old-male.…”
Section: Discussionmentioning
confidence: 99%
“…All were histologically consistent with hybrid schwannoma/perineurioma, had features of high cellularity, nuclear atypia and raised proliferative index which recurred five months after surgical resection as an intraneural perineurioma, showing mitotic activity and proliferative index even higher than that seen in the primary hybrid tumors [30]. Following Requena et al [29] in 2013, Yamada et al [31] reported a hybrid perineurioma and cellular neurothekeoma arising in the nose (unlike Requena’s nine cases, all of which were located in the lips). In 2013, which was indeed a very dynamic year for publication of reports and series of hybrid PNSTs, Kacerovska et al [10] published a series of five cases occurring in the setting of NF Type 1.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several interesting reports describing hybrid peripheral nerve sheath tumors comprising of biphasic (i.e., hybrid) features of neoplastic cells, as follows: a mixture of neurofibroma and schwannoma; schwannoma and perineurioma; perineurioma and granular cell tumor; and so on [1-4]. More recently, Requena et al showed the detailed clinicopathological features of 9 cases of a benign cutaneous plexiform nerve sheath tumor with hybrid characteristics of perineurioma and cellular neurothekeoma, given the name as a benign cutaneous plexiform hybrid tumor of perineurioma and cellular neurothekeoma ( HPN ), all of which were peculiarly located on the lips [1].…”
Section: Letter To the Editormentioning
confidence: 99%
“…More recently, Requena et al showed the detailed clinicopathological features of 9 cases of a benign cutaneous plexiform nerve sheath tumor with hybrid characteristics of perineurioma and cellular neurothekeoma, given the name as a benign cutaneous plexiform hybrid tumor of perineurioma and cellular neurothekeoma ( HPN ), all of which were peculiarly located on the lips [1]. Herein we reported an extremely rare and first case of HPN of the nose occupying the dermis to superficial subcutis as a well-demarcated nodule.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation